Contributions from European symbolic interactionists reflections on methods - Müller, Thaddeus (Studies in symbolic interaction ;, 2015)
The papers in this volume were presented in at the third conference of the European society for the study of symbolic interaction (SSSI). The theme of the 2012 conference was "Conflict, cooperation and transformation in everyday life. The fifteen papers presented across this volume and volume 45 cover a diverse range of topics, which are divided into two main categories: "Reflections on Methods" and "Conflict and Cooperation", this volume focuses on the former. The central issue of the first four papers is how we navigate our emotional, analytical and political selves in the social worlds that we study. How do we relate to those we observe and interview? How do we deal with issues of power, suffering and politics? The following three papers provide a critical analysis of Geertz' 'Thick Description', perspectives on obesity in modern society and an analysis of the relationship between police officers and licensed marijuana coffee shop owners in Rotterdam. Contributing authors to this volume and the next come from Belgium, Canada, Sweden, the US, the Netherlands and Germany, suggesting the thriving diversity of European SSSI in terms of its research themes and methods.